1986
DOI: 10.1113/jphysiol.1986.sp016152
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone effects on lactase expression by rat enterocytes.

Abstract: SUMMARY1. Thyroxine (T4) and triiodothyronine (T3) injected into adult rats causes first an increase and then a decrease in lactase activity measured subsequently in intestinal homogenates of rat jejunum. These changes are not associated with any alteration in intestinal structure or enterocyte migration rate.2. Quantitative cytochemistry shows T4 stimulation and inhibition of lactase activity to take place in upper villus and crypt cells respectively (0-and C-enterocytes). T3 injected into thyroidectomized ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…In addition, the effect on LPH was specific, since no change was observed in the activity of ac-glucosidase (sucrase-isomaltase and maltase). This selectivity was not observed in adult rats fed ad libitum, since both LPH and sucrase activities increased 12 h after a single injection ofT3 or T4 (Hewitt & Smith, 1984 (Hewitt & Smith, 1984). …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, the effect on LPH was specific, since no change was observed in the activity of ac-glucosidase (sucrase-isomaltase and maltase). This selectivity was not observed in adult rats fed ad libitum, since both LPH and sucrase activities increased 12 h after a single injection ofT3 or T4 (Hewitt & Smith, 1984 (Hewitt & Smith, 1984). …”
Section: Discussionmentioning
confidence: 97%
“…A dose 3-4 times this amount was therefore used in the present study. In addition, 150 nmol T3 kg-1 (0-1 ,ug T3 g-1) was the dose used in previous studies to investigate the effect of T3 on intestinal enzyme activity (Hewitt & Smith, 1986). Taking the potency of T3 to be 10 times as great as that of T4, the present dose is also equivalent to the 1 ,ug T4 g-1 used in earlier studies (Hewitt & Smith, 1986;.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of the influence of T4 on lactase expression in adult rats, Hewitt & Smith (1984) found that although the hormone caused a decrease in lactase after 48 h, it resulted in an increase after only 8 h. This increase in enzyme activity was particularly marked in enterocytes which had already moved up the villus and were therefore older. Young pigs kept in the cold maintain enterocytes on the villus for about 5000 more time than their litter-mates in the warm (Dauncey, Ingram, James & Smith, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Frozen jejunal sections prepared from suckling (15-day-old) and post-weaning rats (23 days old, Tsuboi et al 1985;46 days old, Jonas et al 1985) were incubated under initial rate conditions with 5-bromo-4-chloro-3-indolyl fl-D-glucopyranoside as substrate for lactase, the amount of substrate hydrolysed then being determined using a Vickers M84 scanning microdensitometer (Hewitt & Smith, 1986). Enterocyte migration rates determined in these same animals by [3H]thymidine injection were 2-6+004 for 15-day-old.and 11-7+009 mh-1 for 23-plus 46-day-old rats (means+s.E.M.…”
Section: Pmentioning
confidence: 99%